Public Speaking: Teknik Berbicara di Depan Umum dalam Mengelola Vokal dan Gesture yang Tepat - Jaini, Jaini; Sa'i, Mad (FKIP Universitas Majalengka, 2025)
Public speaking is an essential skill that supports self-confidence, effective communication, and professionalism, both in educational settings and daily life. However, many individuals, particularly students and youth, still struggle with managing their voice and gestures appropriately when speaking in public. This community service activity aimed to enhance participants’ understanding and skills in public speaking techniques, especially in vocal control and appropriate use of gestures. The target group of this program consisted of young people and students from a local community. The implementation method included interactive training, practical simulations, and evaluations through pre-test and post-test. The results showed improvements in participants’ self-confidence, understanding of public speaking concepts, and their ability to manage voice intonation and body language in a more structured manner. This activity had a positive impact on developing more effective communication potential in various public settings.